Ground improvement - Kirsch, Klaus; Bell, A. L. (CRC Press, 2013)
When finding another location, redesigning a structure, or removing troublesome ground at a project site are not practical options, prevailing ground conditions must be addressed. Improving the ground-modifying its existing physical properties to enable effective, economic, and safe construction-to achieve appropriate engineering performance is an increasingly successful approach. This third edition of Ground Improvement provides a comprehensive overview of the major ground improvement techniques in use worldwide today. Written by recognized experts who bring a wealth of knowledge and experience to bear on their contributions, the chapters are fully updated with recent developments including advancements in equipment and methods since the last edition. The text provides an overview of the processes and the key geotechnical and design considerations as well as equipment needed for successful execution.